Water Resources in the Lancang-Mekong River Basin: Impact of Climate Change and Human Interventions - Chen, Deliang; Liu, Junguo; Tang, Qiuhong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This open access book provides a comprehensive, up-to-date picture of the current state of knowledge covering climate change, surface water change, arsenic pollution, water utilization, water-food-energy nexus, water related hazards, water management, and water governance in the Lancang-Mekong River Basin. Considering the widely concerned fact that the climate change and human intervention induced impacts on water will bring unprecedented threats to human societies and ecosystems, the book intends to support UN$1 (Bs sustainable development goals through sustainable use of water by providing the most accurate and updated information on climate and water changes in a consistent way. Underlying all aspects of the book is a strong commitment to assessing the science comprehensively, without bias and in a way that is relevant to policy but not policy prescriptive. It can provide implications to support decision-makers and stakeholders for integrated water resources management and sustainable development at all levels. .s
Introduction -- Climate Variability and Climate Changes: past and future -- Surface Water -- Arsenic in Hydro-Geo-Biospheres of the Mekong River Delta: Implication for Human Health -- Water resource availability and use in Mainland Southeast Asia .
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Water; Hydrology; Physical geography; Environmental management; Water; Physical Geography; Earth System Sciences; Environmental Management